2007
DOI: 10.1097/sap.0b013e31802c54ef
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Seroma Formation in Breast Reconstruction With Latissimus Dorsi Flaps

Abstract: The latissimus dorsi flap has been widely used in breast reconstruction surgery. Despite its potential advantages such as low donor morbidity and vascular reliability, the complication of donor-site seroma formation frequently occurs. Consecutive 174 patients who underwent breast reconstruction with the latissimus dorsi flap from 2001 to 2006 were retrospectively reviewed. The age, body mass index (BMI), smoking history, timing of reconstruction, type of breast surgery and nodal dissection, and several other i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 17 publications
5
35
0
2
Order By: Relevance
“…Tomita et al reported that the overall incidence of postoperative seroma was 21%, and they suggested that increased age, obesity, and invasive breast surgery are risk factors for postoperative donor-site seroma with LD flap. 11 These results were very similar to ours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tomita et al reported that the overall incidence of postoperative seroma was 21%, and they suggested that increased age, obesity, and invasive breast surgery are risk factors for postoperative donor-site seroma with LD flap. 11 These results were very similar to ours.…”
Section: Discussionsupporting
confidence: 93%
“…20 There were several reports of association between seroma and smoking history, but no direct association was found between them. 11,12 More large-scale and long-term follow-up studies are required to evaluate this in detail.…”
Section: Discussionmentioning
confidence: 97%
“…Serome im Bereich der Latissimusdorsi-Hebestelle sind keine seltene Komplikation [9,34]. Beim Heben eines "extended" M. latissimus dorsi mit größe-rem Fettanteil sind in einer Kohortenstudie mit 43 Patientinnen in 72% der Fäl-le postoperative Serome berichtet worden [9].…”
Section: Fehler Gefahren Komplikationenunclassified
“…Beim Heben eines "extended" M. latissimus dorsi mit größe-rem Fettanteil sind in einer Kohortenstudie mit 43 Patientinnen in 72% der Fäl-le postoperative Serome berichtet worden [9]. Bei konventioneller Hebung des M. latissimus dorsi liegt die Rate in einer Kohortenstudie mit 174 Patientinnen bei 21% [34].…”
Section: Fehler Gefahren Komplikationenunclassified
“…The most common complication is seroma formation, and the incidence of seroma as a complication has been reported to vary, ranging from 1% to 56% [2,3]. Despite such a high incidence, only limited research on donor-site seroma formation has been conducted [4,5].…”
Section: Introductionmentioning
confidence: 99%